Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1016/j.pain.2005.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the P2X7 purinoceptor gene abolishes chronic inflammatory and neuropathic pain

Abstract: The P2X(7) purinoceptor is a ligand-gated cation channel, expressed predominantly by cells of immune origin, with a unique phenotype which includes release of biologically active inflammatory cytokine, interleukin (IL)-1beta following activation, and unique ion channel biophysics observed only in this receptor family. Here we demonstrate that in mice lacking this receptor, inflammatory (in an adjuvant-induced model) and neuropathic (in a partial nerve ligation model) hypersensitivity is completely absent to bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
629
4
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 721 publications
(667 citation statements)
references
References 37 publications
29
629
4
5
Order By: Relevance
“…For instance, ATP is the major mediator of pain signaling in the spinal cord [19] and promotes the release of interleukin 1 and other proinflammatory cytokines during injury [20,65].…”
Section: Pathological Role Of P2x7r In Spinal Cordmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, ATP is the major mediator of pain signaling in the spinal cord [19] and promotes the release of interleukin 1 and other proinflammatory cytokines during injury [20,65].…”
Section: Pathological Role Of P2x7r In Spinal Cordmentioning
confidence: 99%
“…Knock-down studies revealed suppression of tactile allodynia after the injury [66]. A role for P2X7R in the development of neuropathic pain has come from studies where alteration in the P2X7 receptor pathway also shows reduction of neuropathic pain [65]. This receptor is also overexpressed in patients with chronic pain and disruption of the receptor leads to impairment in the production of IL-1β, IL-10, and IL-6, evidencing its strong involvement in inflammatory responses [67,65].…”
Section: Pathological Role Of P2x7r In Spinal Cordmentioning
confidence: 99%
See 1 more Smart Citation
“…Chessell et al. (2005) reported that P2X7 purinoceptor gene is essential for neuropathic pain. Trang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are associated with different pathologies, including tuberculosis, Crohn's disease or bipolar affective disorders (reviewed by [10]). Genetically engineered mouse models lacking P2X7 expression in distinct tissues showed an attenuation of the release of pro-inflammatory cytokines [11], thereby decreasing the incidence and severity of arthritis [12] and reducing inflammatory and neuropathic pain sensitivity [13]. Thus, the P2X7 has attracted considerable interest as a therapeutic target [7,14].…”
Section: Introductionmentioning
confidence: 99%